Estudos de caso: implantação de sistemas ERP - uma análise crítica à luz da metodologia de Project Management - Gil, Maria Gabriela Sobral (2002)
This document constitutes a thesis for a partial fulfillment for getting a master's degree in Public and Business Management. Our subject is an analysis of two case studies about ERP's system implementation and the techniques of Project Management used as a methodology for their implementation. The study states that the use of the Project Management methodology by itself is not enough to guarantee the success of an ERP's system implementation. Other issues, such as the way the organization deals with change, the Change Management methodology presented on projects, the project team management, as well as the building of a project team is dealt within a project affects the success ofan ERP's system implementation. AIso, some cultural features of the organization influence the results obtained as well as leadership of its project managers. The main results of this study are the theoretical building of the thematic support conceming ERP' s system implementation. The use of interviews aiming at verifying the way the issues treated in this study are dealt on ERP' s system implementation projects and how those aspects influence positively or negatively on the success of those projects. The conc1usions from this research show that not only the use of the Project Management methodology is enough to guarantee the success of such projects. The success is not always reached by meeting the initial expectations of cost, time and budget as the Project Management methodology states primarily. Other features treated in this research also contribute to its failure or success such as the project team building, leadership, the Change Management techniques as well as cultural elements.